Sosialisasi Teknologi Tepat Guna Qr Code Dalam Upaya Pelestarian Punden Dan Sumur Windhu Desa Gadel - Aqshal Hasbi Fahreza; Ririt Iriani Setiawati; Putra Perdana (CV. ITTC INDONESIA, 2022)
Service activities of group 75 on thematic community programs University of Pembangunan Nasional Veteran east Java which are located in karangpoh village,tandes sub-district with scheme the tourism village has a significant impact on the local community.the excistence of historical buildings such as Punden and Sumur Windhu become religious tourism for people who are looking for tranquility, but there are still many people around gadel village who don’t have awareness to participate in preserving buildings that are considered sacred by local community.according to the problem, we are students of group 75 UPN, have tried to make people around us understand the history of punden by making QR programs as our first step and community socialization as our next continuing control.The QR code are connected to our group youtube account which are containing of an ancient illustration video. The video is supposed to be the best guide for the next generation to find out the true stories of punden history from the beginning existence.we were using interviews and socializations methods. We are highly expectation that Our compilied programs could be increase the knowledge and the insight of the community about the importance of preserving historical buildings